2019
DOI: 10.1063/1.5115248
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz radiation from multi ion plasma irradiated by two cross focused Gaussian laser beams

Abstract: Terahertz (THz) radiation generation by nonlinear coupling of two color Gaussian laser beams in a plasma with multi-ion species is numerically investigated by taking into account the nonlinearity due to ponderomotive force and space-charge field. By calculating the modification of electron density distribution of such plasma, coupled differential equations governing the evolution of two laser beams' spot size and the outcome THz wave amplitude are established. The influence of the ionic species density and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The external dc magnetic field used to increase the field of emitted radiations [59]. Jafari et al have investigated that the generation of THz radiation by nonlinear coupling of two color laser beam which have Gaussian field in a plasma with multi-ion species through ponderomotive force on laser in plasma [60]. The radiated THz emission strongly depends on the density of ionic species.…”
Section: Beat Wave Schemesmentioning
confidence: 99%
“…The external dc magnetic field used to increase the field of emitted radiations [59]. Jafari et al have investigated that the generation of THz radiation by nonlinear coupling of two color laser beam which have Gaussian field in a plasma with multi-ion species through ponderomotive force on laser in plasma [60]. The radiated THz emission strongly depends on the density of ionic species.…”
Section: Beat Wave Schemesmentioning
confidence: 99%
“…The space-charge field (SCF) [1][2][3][4][5][6] is an important physical factor in electronic vacuum devices, particle accelerators [7][8][9][10][11][12], free electron lasers (FEL) [13] and plasma systems [14][15][16][17][18]. It is generated by electrostatic interaction between charged particles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, many attempts have been made to relate THz generation to the nonlinear laser-plasma interactions [18][19][20][21]. The generation of THz radiation from laser-induced filaments has been studied by means of numerical methods [22][23][24][25][26][27][28][29][30]. Recently, in a theoretical study carried out by Kumar et al [31], a significant enhancement in THz amplitude was reported due to the self-focusing of an amplitude-modulated Gaussian laser pulse propagated in a rippled plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Further, in order to get close to the real conditions of plasma, Misra et al [35] took into account a multi-ionized plasma with two different species and investigated the self-focusing using an analytical model. The effects of the space-charge field due to the density change of ionic species and also the charge composition on the beam dynamics of lasers and subsequently THz treatment in a multi-ionized plasma were also studied in an another work by Jafari et al [27]. So far, different aspects of the initial parameters' effect on THz yield have been investigated; however, there still exist unknowns relevant to plasma-based THz wave generation, which should be thoroughly analyzed for experimental applications.…”
Section: Introductionmentioning
confidence: 99%